PELATIHAN PENGEMBANGAN SOAL HIGHER ORDER THINGKING SKILL (HOTS) BAGI GURU GURU DI KECAMATAN MUARA GEMBONG KABUPATEN BEKASI - Massus Subekti; Soeprijanto; Rudy Prihantoro; Priyono; Rian Pratama; Brenden F.I (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract This training in the framework of implementing P2M aims to improve teachers' abilities in developing high-level reasoning questions (High Order Thinking Skill/ HOTS). The problem behind this training is that it feels increasingly urgent in facing the 21st Century Era that schools or educational institutions strengthen students' abilities in critical thinking, finding solutions to problems faced by students and the ability to conclude and decide matters related to their future. It is believed that this training will be effective through habituation to students in dealing with HOTS questions. The problem is that there are still many teachers who need to improve their abilities in developing HOTS questions. For this reason, training on developing HOTS questions is needed for teachers. The training was carried out in Muara Gembong District, Begasi Regency through the Community Service Program (P2M) scheme. Jakarta State University. The 2022 training was attended by 15 teachers consisting of 6 elementary school teachers, 6 junior high school teachers and 3 middle school teachers. The training method used is direct learning (offline). The results of the training show that the average value of the Pree Test results is 39.5 and the average value of the Post Test results is 64.6 points. So that this training is able to increase the average value of participants by 28.7 points or increase from less to enough categories. Conclusion This training data stated quite successful. Recommendations Training on the development of HOTS questions for teachers needs to be continued with more participants using methods appropriate to the number and conditions of the participants. Based on the discussion and analysis of the training results data, it can be concluded that with proper training the problems of teachers who are still constrained in developing High Order Thinking Skill (HOTS) questions can be reduced, so that training on developing Hots questions for teachers can be used as a solution. Abstrak Pelatihan dalam rangka pelaksanaan P2M ini bertujuan untuk meningkatkan Kemampuan guru dalam mengembangkan soal soal penalaran tingkat tinggi (High Order Thingking Skill/ HOTS). Permasalahan yang melatar belakangi pelatihan ini adalah dirasa semakin mendesaknya dalam menghadapi Era Abad 21 sekolah atau lembaga pendidikan melakukan penguatan Kemampuan peserta didik dalam hal berpikir kritis, mencari solusi atas permasalahan yang dihadapi siswa dan kemampuan menyimpulkan dan memutuskan hal hal yang berhubungan dengan masa depannya. Pembekalan tersebut diyakini efektif dilakukan melalui pembiasaan kepada peserta didik untuk menghadapi soal soal HOTS. Permasalahannya masih banyak guru yang perlu ditingkatkan kemampuannya dalam mengembangkan soal soal HOTS, Untuk itu diperlukan pelatihan pengembangan soal Hots untuk guru. Pelatihan dilakukan di Kecamatan Muara Gembong Kabupaten Begasi melalui skema Program Pengabdian Masyaraaat ( P2M).UniversitasNegeri Jakarta. Pelatihan tahun 2022 diikuti oleh 15 orang guru terdiri dari 6 Guru SD ,6 Orang guru SMP dan 3 orang guru Sekolah Menengah. Metode pelatihanyang digunakan adalan pembelajaran langsung (Luring). Hasil Pelatihan menunjukan bahwa Nilai rata rata hasil Pree Test sebesar 39,5 dan Nilai rata rata hasil Post Test sebesar 64,6 poin. Sehingga pelatihan ini mampu menaikan Nilai rata rata peserta sebesar 28,7 poin atau menaikan dari kategri kurang menjadi cukup. Kesimpulan Pelatihan ini data dinyatakan cukup berhasil. Rekomendasi Pelatihan pengembangan soal HOTS untuk guru perlu terus dilakukan dengan peserta yang lebih banyak dengan metode yang sesuai dengan jumlah dan kondisi peserta. Berdasarkan pembahasan dan analisis data hasil pelatihan dapat disimpulkan bahwa dengan pelatihan yang tepat permasalahan guru yang masih terkedala dalam mengembangkan soal soal High order thinking Skill (HOTS) dapat dikurangi, sehingga pelatihan pengembangan soal soal Hots untuk guru dapat dijadikan solusi.